Anesthetic challenge in the aftermath of a Pandemic: Giant ovarian tumor (35 Kg) - Pereira, Sofia (Journal of the Portuguese Society of Anesthesiology, 2023)
A 59y woman was scheduled for exploratory laparotomy to remove a giant ovarian neoplasm. Medical history relevant to anemia (9 mg/dL) and coronary heart disease. In pre anesthetic consultation she reported short of breath (grade 1 in mMRC 1) and functional capacity >4 METs. Physical examination relevant to peripheral edema and last transthoracic echocardiography with a normal ejection fraction (56%). Surgery was scheduled after gynecology, anesthesia and general surgery discussion. Balanced general anesthesia was conducted with a rapid sequence induction. Maintenance with sevoflurane,rocuronium e fentanyl 1,2. After endotracheal intubation, volume-controlled ventilation was setted to protective ventilation: low tidal volumes and high respiratory rate (15-18).3 During surgery, peak inspiratory pressure (PICO) with 30 cmH2O was observed. She kept hemodynamically stable. After giant tumor resection (35kg) peak inspiratory pressure dropped, and increased the mean arterial blood pressure and urinary output. No major perioperative cardiorespiratory complications were observed, like pulmonary re-expansion.1,2